2001
DOI: 10.4049/jimmunol.166.4.2734
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Inducible Nitric Oxide Synthase Exacerbates Erosive Joint Disease

Abstract: NO is an essential cytotoxic agent in host defense, yet can be autotoxic if overproduced, as evidenced in inflammatory lesions and tissue destruction in experimental arthritis models. Treatment of streptococcal cell wal1-induced arthritis in rats with NG-monomethyl-l-arginine (l-NMMA), a competitive nonspecific inhibitor of both constitutive and inducible isoforms of NO synthase (NOS), prevents intraarticular accumulation of leukocytes, joint swelling, and bone erosion. Because increased inducible NOS (iNOS) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(78 citation statements)
references
References 27 publications
(38 reference statements)
3
72
0
3
Order By: Relevance
“…Alternatively, L-NIL (3 mg/kg) was administrated i.p. daily (48). Comparison between oral and i.p delivery of inhibitors yielded similar levels of inhibition of NO production.…”
Section: Effects Of Nos Inhibitors During Eae Inductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Alternatively, L-NIL (3 mg/kg) was administrated i.p. daily (48). Comparison between oral and i.p delivery of inhibitors yielded similar levels of inhibition of NO production.…”
Section: Effects Of Nos Inhibitors During Eae Inductionmentioning
confidence: 85%
“…In a second study the specific iNOS inhibitor, L-NIL, was added to the drinking water (100 g/ml) (19, 48) 0 -1 days after immunization for 8 consecutive days. Solutions were prepared daily, fluid consumption in both L-NIL-treated and untreated mice was monitored due to changes in water consumption during the development of disease symptoms, and doses of L-NIL were adjusted accordingly (48). Alternatively, L-NIL (3 mg/kg) was administrated i.p.…”
Section: Effects Of Nos Inhibitors During Eae Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although iNOS has been implicated in the pathogenesis of certain inflammatory diseases, such as arthritis, SLE and irritable bowel syndrome, 62 a number of studies have demonstrated a protective effect of NO against several conditions characterised by inflammation, such as glomerulonephritis, 63 acute hepatic necrosis, 64 arthritis, 65,66 endotoxaemia 64 and acute lung injury 67 in vivo (reviewed by Clancy and Abramson 62 ). Most studies attribute these effects to the wide range of general anti-inflammatory properties of NO, as reviewed by Granger and Kubes, 9 and are outwith the scope of this review.…”
Section: In Vivo Effects Of No and Its Therapeutic Potentialmentioning
confidence: 99%
“…Naive OT-II transgenic T cells, transferred to congenic hosts, were challenged with mOVA, accompanied by continued (daily) injections of the inhibitors 1400W (16) or L-NIL (17) or the vehicle control. Cell recoveries were assessed in circulation of immunized mice on days 4 and 14 after the first challenge.…”
Section: Inos Limits Survival Of Ag-reactive Tem Effectorsmentioning
confidence: 99%